Hypoxia Promotes Glioma Stem Cell Proliferation by Enhancing the 14-3-3β Expression via the PI3K Pathway - Weidong Cao; Qiang Zhou; Hongwei Wang; Wei Rao; Gang Cheng; Peng Wang; Shengli Guo; Bin Ren; Jianning Zhang (Journal of Immunology Research)
Glioma is a serious fatal type of cancer with the shorter median survival period and poor quality of living. The overall 5-year survival rate remains low due to high recurrence rates. Glioma stem cells (GSCs) play the important roles in the development of gliomas. Examination of the numerous biomarkers or cancer-associated genes involved in the development or prevention of glioma may therefore serve the discovery of novel strategies to treat patients with glioma. Hypoxia induced by using CoCl2 application and 14-3-3β protein knockdown by specific small interfering RNA transfection were performed in GSCs both in vitro and in vivo to observe their role in glioma progression and metastasis occurrence by using western blot analysis and MTT assay. The results demonstrated that CoCl2 application enhanced the 14-3-3β protein expression and mRNA levels via the PI3K pathway in GSCs. Furthermore, hypoxia promoted GSC cell proliferation and activated the expression of proliferating cell nuclear antigen, which was inhibited following 14-3-3β knockdown. In addition, tumor growth in mice was enhanced by CoCl2 application but reversed following 14-3-3β knockdown, which also enhanced GSC cell apoptosis. In conclusion, the present study demonstrated that hypoxia promoted glioma growth both in vitro and in vivo by increasing the 14-3-3β expression via the PI3K signaling pathway. 14-3-3β and HIF-1α may therefore be considered as the potential therapeutic target to treat patients with glioma.